Pengaruh Latihan Kecepatan Reaksi Terhadap Ketepatan Kiper Menangkap Bola Tendangan Penalti Pada Ekstrakurikuler Futsal Di Sma Negeri 01 Kota Bengkulu - Achmad Junaidi; Dody Ertanto; Martiani Martiani; Muhammad Sidik Juarsa (Educative Sportive, 2026)
This study aims to determine the effect of reaction speed training on the accuracy of goalkeepers in catching penalty kicks in futsal extracurricular activities at SMA Negeri 01 Kota Bengkulu. This study is quantitative in nature, using a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of eight futsal goalkeepers selected from extracurricular participants. The research instrument used an observation sheet for penalty ball catching skills, which assessed perfect catches, imperfect catches, and failed catches. The data were analyzed using normality, homogeneity, and t-tests to determine the significance of the differences in the results before and after the treatment. The results showed that reaction speed training had a significant effect on improving the accuracy of goalkeepers in catching penalty balls, with a t-value of -12.263 and a p- value < 0.05. This training improved the coordination between perception and motor response, accelerated reactions to the direction of the ball, and fostered mental readiness such as concentration and confidence. Thus, reaction speed training has been proven effective in improving the performance of futsal goalkeepers. Researchers recommend that reaction speed training programs be included in the futsal extracurricular curriculum, especially for goalkeepers. Further research with a larger sample size is recommended to reinforce these findings.